Development of Ethnoscience-Based Student Worksheet Using the Guided Inquiry Learning Model to Increase Students' Learning Motivation and Scientific Literacy: A Review - Januarti, Isna Mutia; Muliyadi, Lalu (Balai Publikasi Indonesia, 2024)
Education is a process of sharing knowledge, knowledge, value conversion, character formation with various supporting aspects with a specific aim in the plan to develop human potential. Currently, many students are unable to apply the results of chemistry learning in their daily lives, this can be triggered by inadequate selection of learning resources, resulting in low student motivation and scientific literacy. This requires a teacher's creativity in the learning process so that the quality of students' learning can increase. One way that can be done is to link learning materials with local culture which can later increase students' scientific knowledge and increase students' motivation and scientific literacy. This research aims to find out learning LKPD by applying ethnoscience learning to chemistry material. The method used in this research is a literature review. Based on the literature review that has been carried out, it can be concluded that selecting appropriate and ethnoscience-based learning resources ranging from 63.76 to 97.15 can improve students' scientific literacy abilities.